2009
DOI: 10.1007/s10584-009-9578-2
|View full text |Cite
|
Sign up to set email alerts
|

Climatic trends in Israel 1970–2002: warmer and increasing aridity inland

Abstract: Climatic trends in Israel during the period 1970-2002 were studied in detail on the basis of three parameters: average annual temperature, annual precipitation and the annual aridity (humidity) index P/PET (P = Precipitation; PET = Potential Evapotranspiration). Significant warming is evident in all 12 evaluated meteorological stations, situated in different parts of Israel. Along the Mediterranean coast, the average annual precipitation and P/PET values remained more or less at the same level. However, more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
94
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(104 citation statements)
references
References 16 publications
(17 reference statements)
8
94
0
2
Order By: Relevance
“…There is distinctive evidence of decreasing biomass across a wide range of shrublands, dwarf-shrublands and plantations from the Avisur Highlands (45 cm/yr) southward. Since human disturbance had not increased across the study area (e.g., [33][34][35]), these results support the findings of Ziv et al [50] and Kafle and Bruins [51] and suggesting increasing aridity in desert fringe ecosystems. However, it is important to mention that the finding reported for the areas south of Yatir Forest is the result of the afforestation works initiated by the Forest Commission of the JNF (Jewish National Fund) during the late 1990s in order to combat desertification in this region.…”
Section: Discussionsupporting
confidence: 78%
“…There is distinctive evidence of decreasing biomass across a wide range of shrublands, dwarf-shrublands and plantations from the Avisur Highlands (45 cm/yr) southward. Since human disturbance had not increased across the study area (e.g., [33][34][35]), these results support the findings of Ziv et al [50] and Kafle and Bruins [51] and suggesting increasing aridity in desert fringe ecosystems. However, it is important to mention that the finding reported for the areas south of Yatir Forest is the result of the afforestation works initiated by the Forest Commission of the JNF (Jewish National Fund) during the late 1990s in order to combat desertification in this region.…”
Section: Discussionsupporting
confidence: 78%
“…Consistently with previous research (Vázquez de Aldana et al, 2008;Kafle & Bruins, 2009) we observed that the variation of rainfall amount reflects in the phytomass production of grasslands, since the year with higher summer rainfall had the higher average summer phytomass production and vice versa. likely, of greater nutritional value, since summer rainfall worsens the forage feed value, because of the senescence of summer leaves, which is a mechanism of drought resistance Volaire et al, 2014).…”
Section: Acknowledgmentssupporting
confidence: 92%
“…1a) and runs along the transitional climate zone between the sub-humid Mediterranean climate in the north and semi-arid regions in the south (Fig. 1b, Kafle & Bruins, 2009). The land hosts four phytogeographic zones: Mediterranean, Irano-Turanian (Asian steppes), Saharo-Arabian (Sahara, Sinai and Arabian deserts) and Sudanian (subtropical savannas of Africa) (Danin, 1988).…”
Section: Introductionmentioning
confidence: 99%